Recent Advances for the C–C and C–N Bond Formation in the Synthesis of 1-Phenethyl-tetrahydroisoquinoline, Aporphine, Homoaporphine, and β-Carboline Alkaloids - Puerto Galvis, Carlos E.; Kouznetsov, Vladimir V. (Synthesis, 2017)
Among the existing methods for the synthesis of bioactive and/or complex small molecules, organic transformations such as C–C and C–N bond formation have been significantly developed and exploited for the synthesis of diverse synthetic and natural fused aza-polycycles. The abundance and biological and physical activities of 1-phenethyl-tetrahydroisoquinolines, aporphines, homoaporphines, and β-carbolines have inspired many organic chemists to seek sustainable and efficient protocols for their preparation. However, these methodologies involve multiple steps and in most cases the key reaction step is based on the formation of new C–C and/or C–N bonds, and this is usually the critical step that lowers the yields and selectivity. This review is focused on the advances made in recent years regarding the synthesis of these selected natural fused aza-polycycles, overviewing the substrate scope, limitations, regioselectivity, and chemoselectivity, as well as related control strategies of these reactions, concentrating on developments from 2010 to 2016.1 Introduction2 1-Phenethyl-tetrahydroisoquinolines; Dysoxylum Alkaloids3 Aporphines, Homoaporphines, and Semisynthetic Derivatives4 Harmala and Eudistomin Alkaloids and Their Biological Properties5 Metal-Catalyzed C–C Bond Formation6 Pd-Catalyzed C–C and C–N Bond Formation7 Metal-Catalyzed C–N Bond Formation8 [4+2] Cycloaddition in the Synthesis Of Aporphines9 Tandem C–N/C–C Bond Formation: The Pictet–Spengler Reaction10 Miscellaneous Methods11 Conclusions
Keywords: tetrahydroisoquinolines; aporphines; homoaporphines; carbolines; C–C bond formation; C–N bond formation